Medicated Feed Additives for Swine - Herrman, Tim J.; Sundberg, Paul (My University, 2000)
This publication explains the regulations regarding the use of medicated feed additives and to provide a list of approved drugs and drug combinations, use levels, and indications for use of medicated feed additives for swine.
MF2042_2000_03
Keywords: MF2042; Livestock; MF